Decentralization of the financial management of basic education: Reflections from the context of the municipality of Lubalo (Angola) - Uarinhenga, João; Silva de Oliveira, Rosenilton (Revista Desenvolvimento Social, 2021)
The aim of this article is to reflect on the way in which the Angolan State has developed its project of decentralization of teaching management, specifically with regard to the administration of financial resources with a view to the implementation of the general objectives of national education, recommended in the legislation. It was based on the bibliographic review, documentary analysis and action research, having as empirical field of observation the municipality of Lubalo (Lunda-Norte Province, Angola). It was argued that such a perspective is beneficial for the achievement of local projects aimed at overcoming inequalities, particularly those in the educational field, as demonstrated by data from the city of Lubalo. The final considerations point to the fact that, in the context studied, the implementation of a decentralized administration, although salutary, faces two structuring challenges: budgetary limitations and the policy of distribution of resources from a previous classification of municipalities that favors regions that have greater infrastructure.